Caregiver stress in traumatic brain injury - Blake, Holly (Mark Allen Healthcare, 2013)
Aims Many patients experience physical, behavioural, cognitive and emotional problems following traumatic brain injury (TBI). They may require continuing care for many years, most of which is provided by informal caregivers, such as spouses, parents, or other family members. The caregiving role is associated with a range of adverse effects including anxiety, depression, poor physical health and lowered quality of life. This article explores issues around caregiver stress; highlighting interventions for this group and areas for further research.